Dimensional Analysis of All Units on Intergovernmental Relations Within the Mining Authority (Study on Unlicensed Gold Mining in District of Kuantan Singingi) - Khotami Khotami; Nandang Alamsah Deliarnoor; Utang Suwaryo; Neneng Yani Yuningsih (Universitas of Muhammadiyah Makassar, 2021)
Abstract. This research is located in Kuantan Singingi Regency which is motivated by the busy activities of gold mining without permits (PETI) carried out by the local community. This is driven by promising income so that these activities are used as a livelihood and a lack of public awareness of the dangers of PETI. In addition, the low level of involvement of government actors and community participation has an impact on the weakness of regulations that form the legal basis for mining activities. This study looks at the relationship between government units that work together in managing gold mining based on their authority. The informants of this study were employees of the Riau Province ESDM Service, members of the Riau DPRD, Kuantan Singingi District Polres staff, DLH employees of Kuantan Singingi Regency and the community. The technique of determining the informants was carried out by purposive method by digging in-depth information according to the characteristics of the study. The data collection technique is done by interview, observation and documentation. The data analysis technique was used by applying a qualitative narrative approach that conveyed the results of the analysis related to PETI. The results of the study found that the importance of local regulations on community mining that involves both provincial and district governments. The weakness of the legal regarding the implementation of gold mining activities must be strengthened by coordinative efforts and cooperation between the provincial government, DPRD and district governments by sharing the perceptions, ideas of each actor.Keywords: All Units, Authority, MiningAbstrak. Penelitian ini bertempat di Kabupaten Kuantan Singingi yang dilatarbelakangi oleh ramainya aktivitas pertambangan emas tanpa izin (PETI) yang dilakukan oleh masyarakat setempat. Hal ini didorong oleh penghasilan yang menjanjikan sehingga kegiatan tersebut dijadikan sebagai mata pencaharian dan kurangnya kesadaran masyarakat akan bahaya PETI. Selain itu, rendahnya tingkat keterlibatan aktor pemerintah dan partisipasi masyarakat, berdampak terhadap lemahnya aturan yang menjadi dasar hukum kegiatan pertambangan. Penelitian ini melihat bagaimana hubungan antar unit pemerintah yang bekerjasama dalam mengelola pertambangan emas berdasarkan kewenangan yang dimiliki. Informan penelitian ini yakni meliputi pegawai Dinas ESDM Provinsi Riau, anggota DPRD Riau, Pegawai Polres Kabupaten Kuantan Singingi, Pegawai DLH Kabupaten Kuantan Singingi serta masyarakat. Teknik penentuan informan dilakukan dengan cara purposive dengan menggali informasi secara mendalam sesuai dengan karakteristik penelitian. Teknik pengumpulan data dilakukan dengan wawancara, observasi dan dokumentasi. Teknik analisis data yang digunakan dengan menerapkan pendekatan narasi kualitatif yang menyampaikan hasil analisis berkaitan dengan PETI. Hasil penelitian mendapati bahwa pentingnya peraturan daerah tentang pertambangan rakyat yang melibatkan pemerintah baik provinsi maupun kabupaten. Lemahnya payung hukum tentang pelaksanaan kegiatan pertambangan emas harus diperkuat dengan upaya koordinatif dan kerjasama antara pemerintah provinsi, DPRD dan pemerintah kabupaten melalui penyamaan persepsi, ide dari masing-masing aktor.Kata Kunci: All Units, Kewenangan, Pertambangan